PROBLEMATIKA PEMBELAJARAN JARAK JAUH PADA MASA PANDEMI COVID-19 DIJURUSAN TADRIS IPS IAIN PONOROGO ANGKATAN 2020 - Mardayanti, Tia (Muara Aksara: Jurnal Ilmiah Multidisipliner, 2021)
The era of the Covid-19 pandemic has hit the world, including Indonesia. This covid pandemic has affected several aspects of life, including education in the IPS tadris department of IAIN PONOROGO batch 2020. Educational institutions require the process of learning activities to be carried out remotely, namely so that students carry out teaching and learning activities even though students are at home. In this case, educators must shape learning through the use of online media. In addition, this distance learning process can accommodate the teaching and learning needs of students majoring in Tadris IPS IAIN PONOROGO, to develop their skills even though it is very difficult to develop student skills. The purpose of this research is to review the problems that occur in distance learning in the Social Sciences Department of IAIN PONOROGO class of 2020 and find solutions in dealing with the obstacles that have occurred in the learning. The method used in this study is a qualitative research method which is generally in the form of data or information, using interview and observation techniques. The results obtained are that students experience many obstacles, especially on the network or data packets that are minimum or less than optimal.